2014
DOI: 10.1074/jbc.m114.561910
|View full text |Cite
|
Sign up to set email alerts
|

Group VIA Phospholipase A2 Mitigates Palmitate-induced β-Cell Mitochondrial Injury and Apoptosis

Abstract: Background: Lipid-induced ␤-cell loss contributes to type 2 diabetes mellitus (T2DM). Results: Palmitate-induced ␤-cell lipid oxidation, mitochondrial dysfunction, and apoptosis correlate inversely with expression of iPLA 2 ␤, which associates with mitochondria, generates monolysocardiolipin, and lowers oxidized phospholipid content. Conclusion: iPLA 2 ␤ mitigates palmitate-induced ␤-cell mitochondrial injury and apoptosis and may facilitate repair of oxidized lipids. Significance: Understanding lipid-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 111 publications
1
24
0
Order By: Relevance
“…If CL is not only translocated but also oxidized, it may trigger another program, which leads to apoptosis [26]. The mitochondrial phospholipase iPLA 2 β shows preference for oxidized CL molecules, which can protect cells against apoptotic death [73]. Monolyso-cardiolipin (MLCL), the product of this reaction can be re-acylated to CL by the enzyme ALCAT, which is located in the mitochondria-associated endoplasmic reticulum.…”
Section: Turnover Of CLmentioning
confidence: 99%
“…If CL is not only translocated but also oxidized, it may trigger another program, which leads to apoptosis [26]. The mitochondrial phospholipase iPLA 2 β shows preference for oxidized CL molecules, which can protect cells against apoptotic death [73]. Monolyso-cardiolipin (MLCL), the product of this reaction can be re-acylated to CL by the enzyme ALCAT, which is located in the mitochondria-associated endoplasmic reticulum.…”
Section: Turnover Of CLmentioning
confidence: 99%
“…The hydroperoxyl radical, HO 2 ● (i.e., conjugated acid of superoxide) and hydroxyl radical ● OH are capable of initiating non-enzymatic lipid peroxidation, a second line of ROS sources, in which FAs play a pro-oxidant role [ 74 ]. Indeed, hydroperoxyFAs, hydroxyFAs (converted from hydroperoxyFAs by glutathione peroxidase 4, GPX4), and numerous other derivatives of PUFAs coming from enzymatic lipid peroxidation are cleaved from oxidized lipids by phospholipases A2 [ 75 ]. Typically, the shorter lipid peroxidation products (e.g., arachidonic acid metabolites) are pro-inflammatory, while the resolvins coming from the C22 ω-3 PUFAs are anti-inflammatory [ 76 ].…”
Section: Pathology Related To Lcfasmentioning
confidence: 99%
“…More recently, in a study examining the effects of lipotoxicity in ␤ -cells, the monolysocardiolipin content was reported to correlate with iPLA 2 ␤ expression level ( 171 ). The authors suggested that iPLA 2 ␤ contributed to cardiolipin remodeling by excising oxidized PUFA residues from cardiolipin to yield monolysocardiolipin species for reacylation with unoxidized C18:2-CoA to regenerate the native cardiolipin structure and function.…”
Section: Proposed Roles For Ipla 2 ␤mentioning
confidence: 99%